Metonymy as a conceptual and linguistic phenomenon - Bernjak, Elizabeta; Fabčič, Melanija Larisa (Anali PAZU HD, 2022)
The articledeals with the concept of metonymy from the perspective of cognitive linguistics. Metonymy (along with metaphor) used to traditionally be seen as a linguistic »ornament« (ornatus) and it is a common misconception that metonymy is not used in everyday communication. Many consider metonymical expressions as a type of linguistic deviation, because they don´t use words in their expected, literal meaning. And yet speakers don´t find it odd, if they hear or use metonymical expressions in their everyday communication and they can understand, seemingly without any problems, sentences that may be interpreted as senseless, if we consider their literal meaning: I have to read Cankar. The milk tipped over. The buses are striking. These nonliteral expressions are based on a relation of contiguity between the usual reference of the linguistic expression and the content we want to convey. In the article, we understand mentonymy as a cognitive-linguistic phenomenon. For a better understanding of metonymical processes, we first define the various types of metonymical relations, aswell as the concepts of contiguity, domain and conceptual metonymy. Conceptual metonymies are realized in metonymical expressions such as PLACE FOR ITS INHABITANTS: Ravne so sprejele Tino Maze. `Ravne welcomed Tina Maze.´ We illustrate the various types of metonymical concepts with examples from the leading Slovene daily newspaper Delo.